Über die Herkunft des starken Kabeljau-Jahrgangs 1996 in der Nordsee - Wegner, Gerd; Dornheim, Holger; Weber, Wolfgang (1997)
Cod in the North Sea is expected to reach „Safe biological limit“ due to a strong 1996 year-class. The cod fry was seen first as 5 cm fingerlings in the catches during a hydroacoustic survey in the southeastern North Sea. Back-calculations of the water drift show with high probability that the respective spawning ground was situated in the southwestern North Sea.